2016
DOI: 10.3390/ijms17101701
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Various Production Characteristics of Streptococcus thermophilus Strains

Abstract: Streptococcus thermophilus is one of the most valuable homo-fermentative lactic acid bacteria, which, for a long time, has been widely used as a starter for the production of fermented dairy products. The key production characteristics of S. thermophilus, for example the production of extracellular polysaccharide, proteolytic enzymes and flavor substances as well as acidifying capacity etc., have an important effect on the quality of dairy products. The acidification capacity of the strains determines the manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 102 publications
(229 reference statements)
3
45
0
Order By: Relevance
“…Meanwhile, this bacterium could synthesize some beneficial molecules, such as exopolysaccharide (EPS), aromatic compounds, and formic and folic acids, which contribute to many desirable production characteristics of dairy products including viscosity, texture, flavor, and water holding capacity, etc. (Hols et al, 2005;Cui et al, 2016Cui et al, , 2017. Furthermore, it has been confirmed that S. thermophilus has various health benefits such as antiinflammatory activity, antimicrobial activity, antioxidant activity, as well as immunomodulation (Junjua et al, 2016;Cui et al, 2017;Uriot et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Meanwhile, this bacterium could synthesize some beneficial molecules, such as exopolysaccharide (EPS), aromatic compounds, and formic and folic acids, which contribute to many desirable production characteristics of dairy products including viscosity, texture, flavor, and water holding capacity, etc. (Hols et al, 2005;Cui et al, 2016Cui et al, , 2017. Furthermore, it has been confirmed that S. thermophilus has various health benefits such as antiinflammatory activity, antimicrobial activity, antioxidant activity, as well as immunomodulation (Junjua et al, 2016;Cui et al, 2017;Uriot et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…The carbohydrate utilization and sugar transport systems of CS5, CS9, CS18, and CS20 were analyzed (Figure 5). S. thermophilus takes up carbohydrates through a phosphoenolpyruvate (PEP)-phosphotransferase system (PTS) or a secondary transport system (Cui et al, 2016). The PEP-PTS consists of a PEP-dependent phosphotransferase (enzyme I, EI), a histidine-containing phosphocarrier protein (HPr, heat-stable protein), and a sugar-specific permease (transporter), which is a membrane-bound complex known as enzyme II (EII).…”
Section: Carbohydrate Utilization and Sugar Transport Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial step in EPS biosynthesis is the transport of sugars from the external environment into the cytoplasm 16 . The general transport systems found in S. thermophilus 1275 are group translocation systems, primary transport systems and secondary transport systems 18 . Group translocation systems are dependent on phosphoenolpyruvate (sugar) phosphotransferase (PEP-PTS).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of the sugars transported into the cytoplasm determines its fate. Nucleotide sugars that lead to EPS biosynthesis are formed from sugar-1-phosphates, while sugar-6-phosphates enters glycolytic pathway 18 . In S. thermophilus 1275, glucose and sucrose are transported into the cell using PEP-PTS transporters that lead to the formation of sugar-6-phosphates.…”
Section: Discussionmentioning
confidence: 99%